Anisotropic cloud string cosmological model with five-dimensional kaluza-klein space-time - Ray, Pranjal Kumar; Roy Baruah, Rajshekhar (Frontiers in Astronomy and Space Sciences, 2022)
Anisotropic cloud string cosmological models has been investigated in the context of five dimensional Kaluza- Klein space time. In this paper the energy momentum tensor is generated by rest energy density and tension density of the string with particle density attached to them. To obtained the exact solutions of the Einstein field equations we assumed a scale factor $a(t) = e^{\frac{1}{β} \sqrt{2β t + c}}$ where $β $ and $c$ are positive constant, which yields a variable deceleration parameter (DP) $q = - \frac{a\ddot{a}}{\dot{a}^{2}} = β H + α$. The physical and geometrical behavior of the models is also discussed in detail.